Managing paradoxes, dilemmas, and change: A case study to apply the Yin Yang wisdom in Western organizational settings. Issue 2 (8th May 2018) - Pauluzzo, Rubens; Guarda, Marta; De Pretto, Laura; Fang, Tony
Abstract : Purpose: Drawing on Fang's (2012) Yin Yang theory of culture while taking up the roadmap proposed by Li (2016) for applying the epistemological system of Yin Yang balancing to complex issues in management research, in general, and to paradoxical issues, in particular, the purpose of this paper is to explore how organizations and individuals in the West can balance cultural paradoxes and manage culture dilemmas through the lens of Yin Yang wisdom. Design/methodology/approach: The paper is based on a qualitative case study. Data are gathered through interviews, documents, and field observations in four subsidiaries of an Italian insurance multinational corporation and were analyzed according to the three parameters, i.e., situation, context, and time (Fang, 2012). Findings: The findings show how the integration and learning from seemingly opposite cultures and sets of values lead the organization and individuals to balancing cultural paradox and managing cultural dilemma effectively. With regard to situation, the authors find that both organizations and customers choose the most relevant value(s) to take advantage of specific events or circumstances, and that different value orientations can coexist. As for context, the authors show that organizations can adapt their values either through suppression and/or promotion, which can foster individuals to find new balancing within the paradox. In terms of time, the authors show that the process of learning from other cultures over time can play a role in the shift of people's and organizations' choices of attitudes and value orientations. Originality/value: The paper suggests the relevance and usefulness of adopting Yin Yang wisdom to uncover the dynamic process of cultural learning in Western scenarios.